Lipoprotein (a) and coronary heart disease: a prospective case-control study in a general population sample of middle aged men. Issue 6763 (1st December 1990) - Rosengren, A; Wilhelmsen, L; Eriksson, E; Risberg, B; Wedel, H
Abstract : OBJECTIVE--To examine the association between the serum lipoprotein (a) concentration and subsequent coronary heart disease. DESIGN--Prospective case-control study based on a six year follow up of a general population sample of men aged 50 at baseline in 1983-4. Serum samples were frozen at the time of the baseline examination and kept at -70 degrees C for six years, after which the lipoprotein (a) concentrations in the samples were measured in cases and controls. SETTING--City of Gothenburg, Sweden. SUBJECTS--26 Men, from a general population sample of 776 men, who had sustained a myocardial infarction or died of coronary heart disease during the six years and 109 randomly selected controls from the same sample who had remained free of myocardial infarction. In neither cases nor controls was there a history of myocardial infarction at baseline. MAIN OUTCOME MEASURES--Proportion of myocardial infarction or deaths from coronary heart disease, or both, in relation to the serum lipoprotein (a) concentration. RESULTS--Men who suffered coronary heart disease had significantly higher serum lipoprotein (a) concentrations than controls (mean difference 105 mg/l; 95% confidence interval 18 to 192 mg/l). Men with the highest fifth of serum lipoprotein (a) concentrations (cut off point 365 mg/l) suffered a coronary heart disease rate which was more than twice that of men with the lowest four fifths of concentrations. Logistic regression analysis showed the serum lipoprotein (a) concentration to be significantly associated with coronary heart disease independently of other risk factors. CONCLUSION--The serum lipoprotein (a) concentration in middle aged men is an independent risk factor for subsequent myocardial infarction or death from coronary heart disease.